(untitled) (Journal of Pathology of Nepal, 2011)
Background: Breast cancer is the common malignant lesion in women. Fine needle aspiration cytology has high sensitivity and specificity and is a simple, rapid and safe method to diagnose breast lesions. The aim of the study was to categorize breast lesions and correlate the Fine needle aspiration cytology diagnosis with histopatholoical findings. Materials and Methods: This was a retrospective study done in department of Pathology of Institute of medicine, Trivuwan university teaching hospital, from January 2007 to December 2010. There were 1403 FNAC cases and 469 histopathology cases. Fine needle aspiration correlation with histopathology was done in 249 cases. All the cases were categorized according to risk for cancers: Unsatisfactory sample, Inflammatory breast disease Benign proliferative breast disease without atypia, Benign proliferative breast disease with atypia, Suspicious for malignancy and Malignant lesions. Results: Benign breast lesions were common in the age group of 21-30 years and malignant breast lesion common in the age of 41-50 years of age. In our study fibroadenoma was most common benign lesion and ductal carcinoma was the most common malignant lesion. The sensitivity and specificity of FNAC for malignancy were found to be 98.2% and 98.5% respectively. Conclusion: Fine needle aspiration cytology is highly sensitive and specific technique for diagnosis of most of the malignant and benign breast lesions. Keywords: Fine needle aspiration cytology; Breast lesion; Breast cancer; Fibroadenoma DOI: http://dx.doi.org/10.3126/jpn.v1i2.5408 JPN 2011; 1(2): 131-135